Evaluating Storage Stability of Pomegranate (Punica granatum L.) and Orange (Citrus sinensis) Juices: A Comparative Temperature-dependent Analysis - Thakur Deeksha; Singh Karuna; Rastogi Mayuri (BIO Web of Conferences)
Fruit juices are famous for their excellent nutritional and sensory properties yet suffer from degradation during storage. The preservation of juice stability depends heavily on temperature because it affects the physicochemical properties alongside bioactive components and sensory attributes throughout storage. Researchers conducted this study to examine how two storage temperatures (4 ± 1 °C and 25 ± 2 °C) affected the physicochemical characteristics and biochemical and sensory qualities of pomegranate and orange juices during a 90-day storage period. The researchers pasteurized fresh pomegranate and orange juices and stored them at refrigerated temperatures ((4 ± 1°C) along with ambient temperature (25 ± 2°C) Analysis evaluated pH, moisture content, ash percentage, total soluble solids (TSS), titratable acidity (TTA), sedimentation index, total phenolic content (TPC), DPPH radical scavenging activity, and ascorbic acid retention every 15-days. A 9-point hedonic/rating scale was used to perform the sensory analysis. A one-way ANOVA determined statistical significance for results that were considered significant when p values were less than 0.05. The measured parameters were all significantly affected by storage temperature. The acidity, antioxidant activity, and phenolic content were better preserved when stored at 4 ± 1°C compared to when stored at 25 ± 2°C. The biochemical stability of pomegranate juice exceeded that of orange juice, particularly in terms of the TPC and DPPH activity. During storage sensory scores reduced throughout while samples stored under ambient conditions experienced faster deterioration in color, taste, and overall acceptability. Refrigerated storage helped delay physicochemical transformations while maintaining sensory attributes. The stability of fruit juices improves with low-temperature storage because it reduces nutrient loss while limiting oxidation and maintaining organoleptic properties.